2015
DOI: 10.1039/c5ra11366k
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt hydroxide [Co(OH)2] loaded carbon fiber flexible electrode for high performance supercapacitor

Abstract: Cobalt hydroxide nanoflakes are uniformly loaded on flexible carbon fiber (CF) paper, and provide good electrical connectivity to the current collector for supercapacitor. The unique porous nanostructure offers low ion diffusion and charge transfer resistances in the electrode. The effect of loading mass on electrochemical properties is investigated. The electrode with a mass loading of 2.5 mg/cm 2 shows the maximum specific capacitance of 386.5 F/g at a current density of 1 mA/cm 2 . Also the same electrode c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…6 (a,b). Figure 6(a) indicates that, the GCF-based Co(OH) 2 electrode possesses moderate specific energy and power compared with previous literature values reported for aqueous electrolyte based Co(OH) 2 on different substrate 14 17 51 52 . The obtained maximum specific capacitance is higher than that reported for Co(OH) 2 with various nanostructures on different substrate and graphene-Co(OH) 2 composites 17 40 53 54 55 56 57 58 , as shown in Fig.…”
Section: Resultssupporting
confidence: 54%
“…6 (a,b). Figure 6(a) indicates that, the GCF-based Co(OH) 2 electrode possesses moderate specific energy and power compared with previous literature values reported for aqueous electrolyte based Co(OH) 2 on different substrate 14 17 51 52 . The obtained maximum specific capacitance is higher than that reported for Co(OH) 2 with various nanostructures on different substrate and graphene-Co(OH) 2 composites 17 40 53 54 55 56 57 58 , as shown in Fig.…”
Section: Resultssupporting
confidence: 54%
“…The charge‐transfer resistance is due to the Faradic redox reaction of the NiCo LDH electrode material along with the exchange of OH − ions. This shows that the Ni 0.76 Co 0.24 LDH electrode had a highly conducting nature and a high charge‐transfer rate between the electrolyte and the active material . The short straight line at low frequency is due to a diffusion process and is not useful for charge storage.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, this strategy also eliminates the limitation due to the poor electrical conductivity and low cycle stability of the TMC, as carbon materials provide the desired conducting pathways for charge transport as well as the chemical and physical stability for a large number of charge–discharge cycles. Consequently, numerous studies are found in the literature combining various CNSs with transition-metal oxides/hydroxides/sulfides, confirming the positive influence of the various CNSs on these transition-metal compounds (TMCs). However, to our surprise, we could not find a single study in which the influence of different CNSs on a particular TMC (oxide/hydroxide/sulfide) has been compared in a systematic manner. Previous reports have only focused on the influence of a particular CNS on a given TMC, making it difficult for one to understand and predict which CNS will be the most effective in improving the electrode properties of a given TMC.…”
Section: Introductionmentioning
confidence: 88%